Effect of Parachute Training with Constant vs Varied Widths on 100-Meter Sprint at North Medan Athletics Club - Hariadi, Hariadi; Fauzi, Muhammad; Ibrahim, Ibrahim; Irfan, M.; Zulaini, Zulaini (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
Objective: To investigate the effects of constant-width and varied-width parachute running training on the 100-meter sprint performance of athletes from the North Medan Athletic Club in 2023 and to determine which training method is more effective. Methods: The entire population of 10 athletes from the North Medan Athletic Club was analyzed. The athletes underwent pretest and post-test measurements for their 100-meter sprint times. They were divided into two groups: one group was trained with constant-width parachute running, and the other group was trained with varied-width parachute running. Pretest and post-test data were analyzed using SPSS 21. Normality tests were conducted to ensure data distribution. Homogeneity of variance was tested to compare the variances between the two groups. A t-test was used to determine the significance of the differences in sprint times before training and after training, as well as the difference between constant and varied-width training. Results: All data were normally distributed and showed homogeneity. The t-test showed a statistically significant improvement in sprint times for athletes in both the constant-width (p < 0.05) and varied-width (p < 0.05) parachute running groups. Furthermore, a significant difference was found between the constant-width and varied-width training methods, with varied-width training showing a greater effect in increasing the sprint speed of athletes at the North Medan Athletic Club.